The Effect of Using Different Concentrations of Nitric Acid and Potassium Nitrate on Stimulating Germination of Two Barley Cultivars - Alaswd, Abdalla (Journal of Pure & Applied Sciences, 2023)
The results showed that there were significant differences between the two cultivars in some studied traits.  Alriyhan cultivar gave the highest values ​​for germination speed, germination ratio, germination strength for the first tool (germination speed), and germination strength for the second tool (germination ratio). While there were no significant differences in root length, wet weight between the two cultivars. The T10 and T6 treatment gave the highest values in germination speed, germination ratio, feather length, dry weight, germination strength of the first tool (germination speed), germination strength of the second tool (germination ratio) when were compared to the rest of the treatments. While there were no significant differences between treatments in root length, feather length, wet weight and dry weight. A laboratory experiment was conducted at the Soil and Fertilization Laboratory of the Soil and Water Department - Faculty of Agriculture - Sebha University. During the winter season 2019/2020, by using a complete random design (CRD) with three replicates to the applied two barley cultivars (Napola, Alriyhan) to the effect of soaking in eleven treatments (T1 without soaking, T2 distilled water soaking 3 hours, T3 distilled water soaking 6 hours, KNO3 T4 5% soak 3 hours, KNO3 T5 10% soak 3 hours, KNO3 T6 5% soak 6 hours, KNO3 T7 10% soak 6 hours, HNO3 T8 0.05 standard soak 3 hours, HNO3 T9 0.1 standard soak 3 hours, HNO3 T10 0.05 standard soaking 6 hours, HNO3 T11 0.1 standard soaking 6 hours).